Pricing, exit, and location decisions of firms: Evidence on the role of debt and operating efficiency - Khanna, Naveen; Tice, Sheri (Journal of Financial Economics, 2005)
We compare pricing and exit decisions of discounters across the business cycle. Cities containing high debt and/or low efficiency firms display higher prices during non-recession years. During recessions, prices increase in cities with less efficient incumbents, but decrease in cities with a mix of high and low debt firms. High debt firms are more likely to exit cities with lower prices, and high debt exiting firms are more likely to be efficient. Apparently, low debt firms strategically lower prices during recessions to force exit of efficient, financially constrained rivals. Weaker competitors face another cost. New entrants locate closer.